Standardisation Of Medium Supplements For Shoot Proliferation In Dendrobium - Sudeep R (Department of Pomology and Floriculture, College of Horticulture, 1994)
Investigations were carried out at the Plant Tissue Culture Laboratory attached to the All India Co-ordinated Floriculture Improvement Project (AICFIP), College of Horticulture, Vellanikkara, during 1991 – 1993 to study the effect of various medium supplements on shoot proliferation in Dendrobium. Axillary buds of Dentrobium nobile were used explants for inoculation. The explants were surface sterilized with 0.1 % mercuric chloride for 10 minutes. Half strength MS medium and VW medium were employed for culture establishment and shoot proliferation. The addition of cytokinin related substances, viz., adenine and adenine sulphate did not have any significant influence on shoot proliferation in either of the media. However, adenine influenced the production of leaves and length of shoots in MS medium, in combination with NAA 2.0 ppm and BA 5.0 ppm. Among the amino acid supplements tried, casein hydrolysate influenced multiple shoot production and leaf production in half strength MS medium. In VW media, peptone enhanced the production of multiple shoots whereas shoot length and leaf production were promoted by casein hydrolysate. Coconut water increased the number of shoots in both half strength MS medium and VW medium. In VW medium length of shoot and number of leaves also were influenced. Tomato juice in combination with NAA and BA produced the maximum number of shoots and leaves in half strength MS medium. It also influenced the shoot production, shoot length and leaf production in VW medium. Spathodea bud liquid influenced shoot elongation and flower extract, the number of leaves, in VW media. Banana pulp could significantly influence the shoot length and leaf number in VW medium alone. Potato extract could not significantly influence shoot production in ½ MS medium, but in VW medium it significantly influenced shoot production, shoot length and leaf number. The shoots produced in media with potato extract was healthier when compared with others. Oscimum leaf extract was found to have no significant influence in either of the media for any of the characters studied. In half strength MS medium, sucrose 3 per cent + NAA 2.0 ppm + BA 5.0 ppm and in VW media glucose 3 per cent + NAA 2.0 ppm + BA 5.0 ppm or sucrose 5 per cent was the best for producing multiple shoots. The shoots were the longest in ½ MS medium with sucrose but in VW medium, glucose was better. For in vitro rooting, KC medium with 3 per cent glucose was the best. The maximum survival percentage of the in vitro plantlets occurred when coconut husk was used as the potting media and when the plantlets were kept in the open. Among all the treatments tried, the best treatment for multiple shoot production was peptone 40 ppm + NAA 2.0 ppm + BA 5.0 ppm in VW medium which produced 16.67 shoots on an average. The longest shoot (5.53 cm) was produced by the combination of tomato juice 10 per cent + NAA 2.0 ppm + BA 5.0 ppm in VW media. The treatment that produced the maximum leaves (6.33) was tomato juice 5 per cent in VW media.